2011
DOI: 10.1186/1471-2474-12-164
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C induces inflammatory mediators and matrix degradation in osteoarthritic cartilage

Abstract: BackgroundTenascin-C (TN-C) is an extracellular matrix glycoprotein that is involved in tissue injury and repair processes. We analyzed TN-C expression in normal and osteoarthritic (OA) human cartilage, and evaluated its capacity to induce inflammatory and catabolic mediators in chondrocytes in vitro. The effect of TN-C on proteoglycan loss from articular cartilage in culture was also assessed.MethodsTN-C in culture media, cartilage extracts, and synovial fluid of human and animal joints was quantified using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 55 publications
(66 reference statements)
3
42
0
2
Order By: Relevance
“…Elevated levels of TN-C have been suggested to induce inflammatory mediators and promote ECM degradation in OA patients [39]. Although TN-C is highly expressed during embryogenesis, its presence is minimal in healthy adult tissues.…”
Section: Inflammation-induced Extracellular Matrix Changes In Ostementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of TN-C have been suggested to induce inflammatory mediators and promote ECM degradation in OA patients [39]. Although TN-C is highly expressed during embryogenesis, its presence is minimal in healthy adult tissues.…”
Section: Inflammation-induced Extracellular Matrix Changes In Ostementioning
confidence: 99%
“…Its expression during OA is, however, highly upregulated [40, 41]. The elevated concentration of TN-C causes a significant effect in the catabolism of the cartilage, resulting in degradation of ECM [39, 40]. Additionally, biglycan fragments in articular cartilage and meniscus and fibronectin fragments in hip and knee synovia have also been found in elevated levels as OA progresses [42–44].…”
Section: Inflammation-induced Extracellular Matrix Changes In Ostementioning
confidence: 99%
“…Tenascin C is an extracellular glycoprotein involved in tissue injury/repair and is upregulated in osteoarthritic cartilage, where tenascin C protein fragments are believed to induce inflammatory mediators and ECM degradation (Patel et al, 2011; Sofat et al, 2012). We found no evidence of tenascin C fragmentation in Matn 3 V194D and Comp DelD469 samples since the examination of matched peptides did not reveal any genotype specific differences in sequence coverage (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…But, these molecules are reappeared in a diverse condition such as tissue injury, wound healing, vascular disease, tumorigenesis and metastasis. Tenascin-C is a modular, multifunctional extracellular matrix (ECM) glycoprotein that is associated with tissue injury and repair (Patel et al, 2011). It was discovered originally in gliomas, muscle tissue and in the nervous system, and called by different names: myotendinous antigen, glial/mesenchymal ECM protein, cytotactin, J1 220/200, neuronectin and hexabrachion (Chiquet-Ehrismann et al, 2003;Patel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tenascin-C is a modular, multifunctional extracellular matrix (ECM) glycoprotein that is associated with tissue injury and repair (Patel et al, 2011). It was discovered originally in gliomas, muscle tissue and in the nervous system, and called by different names: myotendinous antigen, glial/mesenchymal ECM protein, cytotactin, J1 220/200, neuronectin and hexabrachion (Chiquet-Ehrismann et al, 2003;Patel et al, 2011). Recent scientific evidences suggested that mucosal TnC is increased in ulcerative colitis and Crohn's disease, especially in areas of ulceration (Geboes et al, 2001), and sera of patients with active ulcerative colitis and Crohn's disease (Riedl et al, 2001).…”
Section: Introductionmentioning
confidence: 99%